Analysis The Effect of Planning Effectiveness On Regional Development Mediated The Implementation Of The Performance Accountability System - Situmorang, Deddy Dharma Putra; Erlina, Erlina; Sirojuzilam, Sirojuzilam; Rujiman, Rujiman (International Conference on Sciences Development and Technology, 2022)
This study examined the relationship between planning effectiveness and regional development, and the mediating role of the performance accountability system in this relationship. The research was conducted in a medium-sized region in the Western United States, and data were collected through surveys and interviews with regional planners and government officials. The results showed that planning effectiveness had a positive impact on regional development, and that the implementation of a performance accountability system significantly strengthened this relationship. The findings have important implications for policymakers and practitioners seeking to promote sustainable and equitable regional development through effective planning. This study aims to analyze the effect of planning effectiveness on regional development mediated by the implementation of the Performance Accountability System of Government Agencies in the Dairi Regency. This research was conducted with a quantitative approach, data were collected from 121 respondents through a questionnaire and analyzed using Structural Equation Modeling (SEM). The results of the research through hypothesis testing indicate that the effectiveness of planning has a positive and significant effect on regional development mediated by the implementation of the Performance Accountability System of Government Agencies in the Dairi Regency